2019
DOI: 10.29252/sjku.24.5.83
|View full text |Cite
|
Sign up to set email alerts
|

The effect of transcutaneous electrical acupoint stimulation on sleep quality in chronic insomnia disorder

Abstract: Background and Aim: Acupuncture is one of the most common methods of complementary medicine. The purpose of this study was to evaluate the effect of transcutaneous electrical acupoint stimulation on sleep quality in the patients with chronic insomnia. Materials and Methods: This study was a single-blind clinical trial in which 40 patients with chronic insomnia were randomly placed into intervention (TEAS) and control (sham TEAS) groups. The acupuncture points including SP6, HT7 and LI4 were selected according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Regarding the components of sleep quality, in all cases (Including sleep duration, sleep delay, sleep e ciency, daily dysfunction, use of sleeping pills, and mental quality of sleep) except sleep disorders, the method of auricular therapy was effective and there was a signi cant difference between the intervention group and the control group. In their study (2020), Khaledi et al Achieved similar results regarding the effect of acupuncture on sleep quality in chronic insomnia, which was measured by kinematics test (25). In 2019, Ren also considered the effect of auricle therapy on primary sleep disorder to be effective (26).…”
Section: Resultsmentioning
confidence: 88%
“…Regarding the components of sleep quality, in all cases (Including sleep duration, sleep delay, sleep e ciency, daily dysfunction, use of sleeping pills, and mental quality of sleep) except sleep disorders, the method of auricular therapy was effective and there was a signi cant difference between the intervention group and the control group. In their study (2020), Khaledi et al Achieved similar results regarding the effect of acupuncture on sleep quality in chronic insomnia, which was measured by kinematics test (25). In 2019, Ren also considered the effect of auricle therapy on primary sleep disorder to be effective (26).…”
Section: Resultsmentioning
confidence: 88%
“…Backhaus et al (2002) reported the reliability level of PSQI in individuals with first insomnia to be 0.85 through Cronbach's alpha method and 0.87 through the test-retest method. Its reliability in a sample of 40 Iranian patients with chronic insomnia was estimated to be 0.87 (Khaledipaveh et al, 2018). In the present study, the reliability of this questionnaire was calculated to be 0.83, using Cronbach's alpha method.…”
Section: Instrumentsmentioning
confidence: 79%